2014
DOI: 10.1007/s11695-014-1498-1
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience with Customized, Meal-Triggered Gastric Electrical Stimulation in Obese Patients

Abstract: BackgroundWe report our initial gastric electrical stimulation experience using the abiliti® system for the treatment of obese patients followed for 1 year.MethodBetween March 2011 and June 2013, 27 obese patients (BMI 30 to 46 kg/m2) were enrolled in a prospective open label study and implanted with a gastric stimulator. The patients were provided with nutritional support, and sensor-based behavioral feedback.ResultsAt 12 months, percent excess weight loss (%EWL) obtained was 49.3 ± 19.2 % with no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…abiliti® device, IntraPace (Miras et al, 2015) Same as above 27 obese patients with BMI 30 to 46 kg/m² 49.3% excess weight loss at 12 months with no significant difference between age and gender. Using a subgroup analysis they showed that stimulation was more effective for patients with a lower BMI (30-40 kg/m²) than for those with a higher BMI.…”
Section: Study Stimulation Paradigm Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…abiliti® device, IntraPace (Miras et al, 2015) Same as above 27 obese patients with BMI 30 to 46 kg/m² 49.3% excess weight loss at 12 months with no significant difference between age and gender. Using a subgroup analysis they showed that stimulation was more effective for patients with a lower BMI (30-40 kg/m²) than for those with a higher BMI.…”
Section: Study Stimulation Paradigm Main Resultsmentioning
confidence: 99%
“…Rapid and significant effect on glycemic control and blood pressure. abiliti® device, IntraPace (Ladabaum et al, 1998, Chen, 2004 (Greenway andZheng, 2007, Cha et al, 2014) Clinical studies (Horbach et al, 2015, Miras et al, 2015 GES 2 electrodes placed on the serosa of the proximal stomach. Food sensor, transgastric electrode, is placed through the stomach gastric wall: the stimulation is meal-activated The stimulation electrode is implanted on the anterior wall of the stomach.…”
Section: Study Stimulation Paradigm Main Resultsmentioning
confidence: 99%
“…The CLGES system used in this study is designed to deliver intermittent gastric stimulation triggered by a transgastric sensor that senses the entry of food into the stomach. A particular feature of this device is that the intensity of the stimulation can be adjusted according to a personalized schedule, in order to obtain early satiety when the patient eats during the periods of the day when the ingestion of food is permitted and to produce gastric discomfort in case of off‐schedule food intakes . This particular mode of action was designed to reduce both portion sizes at meals and off‐schedule eating episodes, with a comprehensive reduction in unhealthy eating behaviors .…”
Section: Discussionmentioning
confidence: 99%
“…The CLGES system has the ability to collect objective electronic data on food intake and physical activity. These data can be stored, visualized, and used in a program of lifestyle modification . Encouraging preliminary results in patients treated with the CLGES system have been reported, with acceptable weight loss rates and very few complications and side effects .…”
Section: Introductionmentioning
confidence: 99%
“…Patient and medical staff monitor the results and use the information to modify the patient’s behavior. Twelve month data in an open label study of 27 obese subjects (mean BMI 40.0 ± 5.7 kg/m 2 ) showed a mean percent excess weight loss (EWL) of 49.3 ± 19.2 [ 27 ]. It is not possible from the design of the study to determine the effect of the electrical signal versus the effect of food and exercise monitoring on behavioral modifications.…”
Section: History Of Gastric Electrical Stimulationmentioning
confidence: 99%